The Relationship between Religiosity and Emotional Intelligence in Nursing Students at Universitas Negeri Gorontalo - Antu, Mihrawaty S. (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Being a student will definitely encounter various situations and problems. If this condition continues and students whose endurance/resilience when facing problems tends to be weak will threaten their psychological well-being which then results in disruption of mental health so that the ability that must be possessed to be able to survive is emotional intelligence. One of the factors that can create emotional intelligence in a person is educational factors which include religiosity. This study aims to determine the relationship between religiosity and emotional intelligence in Nursing students at Gorontalo State University. This research is quantitative research using a correlational method with a cross sectional approach. The sample in this study was nursing students at Gorontalo State University totaling 85 respondents using the Centrality of Religiosity Scale (CRS) and Wong and Law Emotion Intelligence Scale (WLEIS) questionnaire instruments. The results of this study show that there is a relationship between religiosity and emotional intelligence in Nursing students at Gorontalo State University. Using the Spearman Rank test, the p-value = 0.000 (p < 0.05). It is hoped that this research will provide benefits for students to be able to maintain their religiosity and emotional intelligence so that their understanding of religion can always be used as a basis for managing emotions.